An Analysis of Medical Acupuncture Terminology Translation Procedures In An Article Entitled ‘Safety of Yamamoto New Scalp Acupuncture In Healthy Subjects And The Relationship Between Shoulder Stiffness, Diagnosis Points, And Stimulations Points’from Eng - Yuliawati Kusumaningrum; Neneng Sri Wahyuningsih (Syntax Corporation, 2022)
The study aims to analyze translation procedures of medical acupuncture terminology in an article entitled ‘Safety of Yamamoto New Scalp Acupuncture in Healthy Subjects and the Relationship between Shoulder Stiffness, Diagnosis Points, and Stimulation Points’. The study used the descriptive qualitative method to analyze translation procedures of medical acupuncture terminologies by using the concepts of medical terminologies from Cohen & Depetris (2014) and translation procedures from Newmark (1988). The results show that the medical acupuncture terminologies found in the article (source text) can be grouped into four medical terminology concepts based on Cohen and DePetris’ (2014). They are word part, body system, diagnosis, and treatment. Furthermore, it was also found that most noun phrases (26 data), non-body system (29 data), non-diagnosis (26 data), and non-treatment (24 data) were in medical acupuncture terminology concepts. In the translation (target text), there are five translation procedures that are used to translate the medical terminologies. The translation procedures are transposition (24 data), naturalization (nine data), use of foreign words or phrases in italics procedure (two data)), literal translation (one data), and transference (one data). Based on the findings, the combination of both theories can be used in analyzing or doing medical terminology translation, particularly in acupuncture